Extramedullary Plasmacytoma Diagnosed in an HIV-Positive Patient by an Unusual Clinical Presentation - Paulo de Camargo Moraes; Luiz Alexandre Thomaz; Victor Angelo Martins Montalli; José Luiz Cintra Junqueira; Camila Maria Beder Ribeiro; Luciana Butini Oliveira (Hindawi Limited, 2016)
The aim of this paper is to describe a case report of EMP in an HIV-positive patient. A 44-year-old, dark-skinned HIV-infected woman was referred to the Oral Diseases Treatment Center with a swelling at palate and left gingival fornix in the maxilla. Biopsy was taken and the oral lesion was diagnosed as EMP with well-differentiated plasma cells and restriction of the lambda light-chain. Skeletal survey was performed and no radiograph alterations were observed, thus supporting the diagnosis of EMP. Patient was referred to treatment and after two months of chemo and radiotherapy, an expanding lesion was observed in L5/S1 patient's vertebrae. Biopsy of the spinal lesion was consistent with lymphoma with plasmocitary differentiation, supporting the diagnosis of multiple myeloma (MM). Regarding the medical history, the final diagnostic was an oral extramedullary plasmacytoma with rapid progression into multiple myeloma. It is crucial to emphasize the relevance of HIV infection as a risk factor for both aggressive clinical behavior and unusual clinical presentation of extramedullary plasmacytoma cases.